기혼여성들의 임신동기에 관한 연구 - 조주연; 한승의; 송미승; 전미순; 함미영; Cho, Ju-Yeon; Han, Seung-Eui; Song, Mi-Seung; Jeon, Mi-Soon; Ham, Mi-Young (여성건강간호학회지, 2003)
Purpose: This study is to define the structural patterns of pregnancy motivation of married women. Method: Q-methodology was used on 110 statements collected from interviews with women and a literature review. 38 Q-samples were selected. The Q-samples were administerd to 30 randomized P-sample. Result: Data analysis of Q-type obtained by QUANL program shows three types of subjectivity in the perception of pregnancy motivation. Type 1, $\ulcorner$Family-connection strengthening$\lrcorner$, Pregnancy motivation is characterized by the tendency to make home, to tie family member, to connect couple firmly. Type 2, $\ulcorner$Self-satisfaction$\lrcorner$, Women of this type take pleasure and happiness from child rearing in terms of being a mother and having maternal affection. Type 3, $\ulcorner$Self-centered$\lrcorner$, This type of pregnancy motivation puts on high emphasis on self achievement and they make a family planning suitable for the maternal role. Conclusion: The stronger was women's pregnancy motivation, the more positive were women's pregnancy experience and maternal role attainment. Conclusion: Therefore, When nurses take care of pregnancy women, they should understand the women's psycho-social aspects and then apply a program of nursing intervention to the pregnant women, It is necessary to continue to study on social and psychological problems related to pregnancy.